A propósito de e. (amerhippus) curvidens en el pleistoceno de colombia (1962)
The presence of Equus (Amerhippus) curvidens has been reported not only in the pleistocene of the Sabana de Bogotá but in other places too. The whole material referred to this species has not been preserved in any collection, except for two teeth (P4 and Ml) obtained in Quipile, Depto. de Cundinamarca, Eastern Andes. Both teeth morphologically agree with E. (E.). It can be concluded that the presence of E. (Amerhippus) curvidens remains to be prooved, and, according to the known geographical range, this species might be excluded from the pleistocene fauna of Colombia.